7t-3+4t=-2

Simple and best practice solution for 7t-3+4t=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7t-3+4t=-2 equation:



7t-3+4t=-2
We move all terms to the left:
7t-3+4t-(-2)=0
We add all the numbers together, and all the variables
11t-1=0
We move all terms containing t to the left, all other terms to the right
11t=1
t=1/11
t=1/11

See similar equations:

| (3x-22)^2=0 | | 20=(-1.5r+0.75 | | 1/9x+5=11 | | -(c-4)=13 | | 8(11^(7k))-3=213 | | -16t^2+80t+2=0 | | 1/3x-3=30 | | (8*11^7k)-3=213 | | .11=(x-86)/x | | -68+30k=10(3k-7)+7 | | 0.3x-0.5=2.8 | | -13=-11+x | | 12.95+0.25=21.20m | | 12.95m+0.25=21.20 | | 2(−4x+3)+3x+3=16 | | 2x-8=-23 | | 4x/3=108/x | | N+6=8x4 | | 11/100=(x-86)/x | | n-9=8n+15 | | 0.7x+15=1 | | 8(2x)+4=30 | | 12.95m+0.25m=21.20 | | 3x-15=8x-40 | | 11=(x-86)/x | | 3x-15=8x-49 | | -6-h+10+2h=12 | | 2x+1=3x+4x+23 | | 3+x=9+4 | | 24+c=16 | | p+(3p-5)+(4p+6)= | | 8.88=4.44(x-77) |

Equations solver categories